THE ISSUES OF ENVIRONMENTAL ENGINEERS EDUCATION IN TERMS OF BLOOM’S TAXONOMY - Radomska, M. M.; Chernyak, L. М. (Proceedings of National Aviation University (archive), 2016)
The paper presents the analysis of learning efficiency for environmental engineers. The modern trends in education development demand modification of educational process in higher educational establishments to join the tuning process taking place in Europe. The essence of modification is shown to be shifting from learning requirements definition to building competencies. The existing approaches to formation and evaluation of competencies have been analyzed. The role of taxonomies in planning and evaluation process has been considered and Bloom's taxonomy has been applied for the analysis of environmental engineers training efficiency. The major problems in three domains of education by B.S. Bloom have been defined for the given occupation mastering and potential solutions have been offered.